Economic Fundamentals for Development of International Road Freight Transportation Logistics in the Republic of Belarus under Coronavirus Pandemic - R. B. Ivut; A. S. Zinevich (Наука и техника)
The paper considers an issue of international logistics development in Belarus under world coronavirus COVID-19 pandemic. As a result of analytical reviewing of the up-to-date scientific literature on the problem under study, the expediency is stated for highlighting the logistics of international road freight transportation as an independent area of theoretical research and practical activity. Further development of international road freight transportation logistics in the Republic of Belarus requires a complex economic analysis of the present state and dynamics of the international road freight transportation market, which is the main purpose of the present publication. The paper contains the results of the analysis of the market for international and transit freight road transportation. Separately the paper points out the dynamics of transit goods transportation segment in this market in response to the reorientation of international freight flows. Interconnection is shown between the volume indices of international road freight transit through the territory of Belarus and the dynamics of goods import to the Russian Federation from the EU countries. For the first time a proposal is given to use the methodological tools of systemmatrix diagnostic analysis for investigation of the macroeconomic development process of international road freight transit logistics. The author’s set of initial parameters for the analysis has been formed, and its results are presented on the basis of the data of the State statistical reporting form for 2019–2020. A suggestion is given for joint usage of system-matrix diagnostic tools in combination with author’s methodology for assessing the effectiveness of transit (international) freight transportation while evaluating the competitiveness of economic entities in the industry. The most typical trends of the market development in the short term are stated, taking into account the more complicated market conditions.